Parental Perception of the Impact of COVID-19 on Children’s Psychosocial and Cognitive Development - Chopdat, Habeebah (University of the Witwatersrand, Johannesburg, 2023)
COVID-19 caused a myriad of global problems. This study aimed to establish whether the COVID-19 pandemic and the preventative measures that occurred as a result thereof had an impact on the cognitive and psychosocial development of 6–13-year-old learners in South Africa as per parental perception (N=31). A mixed methods research design was used, and the data collection occurred through an electronic survey consisting of specifically designed Likert scale items to collect numerical data, along with open-ended questions which were posed to collect qualitative data. The data was analysed by means of t-tests and a one-way ANOVA for the quantitative data analysis, whilst a thematic analysis was used to analyse the qualitative data. The t-tests and one-way ANOVA showed that there were no statistically significant differences in the cognitive and psychosocial abilities of children across gender (p>0.05), school type (p> 0.05), and the amount of school missed (p> 0.05). Certain themes emerged through the qualitative analysis including both positive and negative themes relating to the learning situation during the lockdown; behavioural changes were also evident in some of the sample; however, others did not report any differences compared to pre-COVID-19. Additionally, children were reported to have worries and concerns over the pandemic as well as the effects thereof. This study contributes to understanding the long-term effects that the measures associated with a global pandemic have on children. As per this study, it appeared that children’s development amidst a pandemic was not impacted by their socioeconomic status however, due to certain limitations of this study, including the sample recruited not being an accurate representation of the socioeconomic divide in South Africa, further studies are required.
A research project submitted in partial fulfilment of the requirements for the degree of Master of Arts, by coursework and research report in the field of Psychology in the Faculty of Humanities, University of the Witwatersrand, Johannesburg, 15 March 2023.
Keywords: COVID-19; Pandemic; Children; Cognitive; Psychosocial; Virtual learning; Lockdown; Social distancing; UCTD